Economic, Education, and Perception of Parents for Pursuing Education for Their Children - Bahagia Bahagia; Leny Muniroh; Abdul Karim Halim; Rimun Wibowo; M. Azhar Al-Wahid; Zakky Muhammad Noor (Universitas Pahlawan Tuanku Tambusai, 2022)
Education has an important role in human life. This study aims to find out whether the factors of education, economy, and perceptions of education affect the mindset and also the desire of parents to provide education to their children. The research method used is the literature review method. Data collection is done by collecting various sources of scientific research including journals and books. The results showed that parents' perceptions of education influenced the parents' desire to continue their education for their children or not. If the perception of parents is getting better, the parents will send the child to school. Likewise, with economic factors, providing schools for children costs money because schools include costs so that low-income parents consider the sustainability of education for their children. Although there are also parents who continue to send their children to school. While the education factor is a factor that influences parents to provide school to their children. When parents have a higher education then the child will be given a proper education. Even though there are parents who have low education, they still provide proper education for their children.